156k views
0 votes
Thanks for helping...

Thanks for helping...-example-1
User Lastarr
by
5.8k points

1 Answer

4 votes

Answer:

16

Explanation:

Subtracting the given expressions, that is

3b² - 8 - (b(b² + b - 7) ) ← simplify parenthesis

= 3b² - 8 - (b³ + b² - 7b) ← distribute parenthesis by - 1

= 3b² - 8 - b³ - b² + 7b ← collect like terms

= - b³ + 2b² + 7b - 8 ← substitute b = - 3

= - (- 3)³ + 2(- 3)² + 7(- 3) - 8

= - (- 27) + 2(9) - 21 - 8

= 27 + 18 - 21 - 8

= 16

User Michael Yurin
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.